2016
DOI: 10.1016/j.ijotn.2015.08.001
|View full text |Cite
|
Sign up to set email alerts
|

A review of blisters caused by wound dressing components: Can they impede post-operative rehabilitation and discharge?

Abstract: This review highlights that some wound dressings can be the cause of blistering. It also presents the mechanisms by which blisters may be caused by poor choice of dressings. The subsequent impact of the blisters on preventing patient mobility -and hence rehabilitation in terms of physiotherapy -are also identified. The possibility that the clinical sequelae (e.g. delayed wound healing, restricted joint range of motion (ROM), muscle atrophy and increased risk of deep vein thrombosis (DVT)) resulting from this m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Surgical patients who develop postoperative wound complications are at risk for a prolonged hospital stay, which can be an increased burden on both the patients and the health care practitioners who care for them. 3,14 A question that continues to perplex clinicians is why certain patients develop skin problems after surgery. Length of surgery, type of dressing, patient sex and comorbidities, positioning, and other extrinsic and intrinsic factors all may lead to an increased risk for blistering.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Surgical patients who develop postoperative wound complications are at risk for a prolonged hospital stay, which can be an increased burden on both the patients and the health care practitioners who care for them. 3,14 A question that continues to perplex clinicians is why certain patients develop skin problems after surgery. Length of surgery, type of dressing, patient sex and comorbidities, positioning, and other extrinsic and intrinsic factors all may lead to an increased risk for blistering.…”
Section: Discussionmentioning
confidence: 99%
“…A review of the literature on skin blisters specifically related to postoperative dressings found that the occurrence of dressing-related skin injuries varies according to multiple factors, including surgical specialty and type of dressing. 3 A quasi-experimental study of 169 total hip and knee arthroplasty patients found that 22 (13%) developed blistering around the surgical site. 2 In a different study of orthopedic surgery patients, the postoperative blister rate ranged from 6% to 24% depending on the type of dressing.…”
Section: Description Of the Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…Postoperative compression might be clearly beneficial for hemostasis to reduce hematoma formation and blood loss and to reduce edema to control pain and wound healing (365,(371)(372)(373)(374)(375). However, excessive compression can result in nerve palsy, blistering, pressure sore development, and even necrosis (366,376,377). Because the compression force is not easily measureable and the ideal force varies among individuals, a patient's feedback is important to avoid these complications.…”
Section: Postoperative Considerationsmentioning
confidence: 99%
“…This wet environment favors moisture-associated skin damage (maceration) and bacterial contaminations of the wound, especially if the dressing has a mechanical leak (26). Postoperative wound complications or infections may result in increased rehabilitation time (27,28), hospital length of stay as well as morbidity and mortality rates (18,29).…”
mentioning
confidence: 99%